Self and other : object relations in psychoanalysis and literature - Rogers, Robert, 1928- (Psychoanalytic crosscurrents., 1991)
In "Self and Other", Robert Rogers presents a powerful argument for the adoption of a theory of object relations, combining the best features of traditional psychoanalytic theory with contemporary views on attachment behavior and intersubjectivity. Rogers discusses theory in relation both to actual psychoanalytic case histories and imagined selves found in literature, and provides a critical rereading of the case histories of Freud, Winnicott, Lichtenstein, Sechehaye, and Bettelheim.